The oxidative nucleophilic substitution of Hydrogen (ONSH): A theoretical modelling of 2-phenylquinoxaline reacting with organolithium nucleophiles - Cukrowski, Ignacy (University of Pretoria, 2021)
Dissertation (MSc (Chemistry))--University of Pretoria, 2021.